Draft Sixth Five Year Plan (1978-83) on Development of Co-operation in Manipur - Planning Commission (Planning Commission, 1978)
The hilly areas like Manipur have a peculiar Problem. By virtue of its geographical situation and graphical conditions, Manipur State has also its own specific problems effecting the social-economic growth of the people, with these problems of natural factors the Cooperative movement could not flourish the desired extent like that of other advanced states. However with implementation of successive five year plans i.e. 2nd, 3rd and 4th plan it has laid a good foundation for future expansion and growth of Cooperative movement in Manipur. Now it has to play an active role for sustained economic growth of the weaker section of the community, Cooperatives being essentially service institutions, safeguard the interest of both the growers and the consumers.
Department of Co-operation, Government of Manipur